MULTIPOINT SELFADJOINT QUASI-DIFFERENTIAL OPERATORS FOR FIRST ORDER - YILMAZ, BÜLENT (ANKARA UNIV, FAC SCI, 2018)
In the present paper, the aim is to described all selfadjoint extensions of the minimal operator generated by first order linear symmetric multipoint quasi-differential operator expression in the direct sum of weighted Hilbert spaces of vector-functions defined at the semi-infinite intervals by using the Calkin-Gorbachuk method. We have also examine the structure of the spectrum of such extensions.
Keywords: Symmetric and selfadjoint differential operators; multipoint quasi-differential expression; deficiency indices; spectrum